COVID-19–Mediated Electrical Storm Managed With Milrinone in a Vaccinated Patient - Marina Johnston; Spencer Moen; Philip Gentlesk; Rishik Vashisht; Xian Qiao (Annals of Internal Medicine: Clinical Cases)
SARS-CoV-2 infection (COVID-19) can lead to an inflammatory response affecting multiple organs. Ventricular arrhythmias, including ventricular tachycardia and ventricular fibrillation (VF), have been reported in otherwise-healthy individuals who have not been vaccinated. A young, otherwise-healthy man who was vaccinated and recently diagnosed with COVID-19 was admitted for refractory VF. Common pharmaceutical agents for VF were given to no avail. VF resolved with use of low-dose milrinone infusion. An inotropic agent usually used in patients with heart failure, milrinone also possesses proven anti-inflammatory effects, which may have allowed it to succeed where the traditional agents failed.